PENGEMBANGAN MEDIA PEMBELAJARAN DIGITAL MENGGUNAKAN MACROMEDIA FLASH 8 PADA MATA PELAJARAN TEKNOLOGI INFORMASI KOMUNIKASI KELAS VII DI SMP DHARMA BHAKTI PALEMBANG - Agung, Sandi; Wijaya, Alex (Faculty of Teacher Training and Education, 2024)
The problem of this research is how the results of the development of digital learning media using Macromedia Flash 8 in class VII junior high school information communication technology subjects are valid and effective. The aim of this research is to produce a product in the form of digital learning media using Macromedia Flash 8 in class VII SMP information and communication technology subjects. The method used in development is the ADDIE model (Analysis, Design, Development, Implementation and Evaluation). The ADDIE model is very synonymous with developing a product for use in learning. The development results show that digital media using Macromedia Flash 8 which was developed by the maker of this product meets the very valid criteria. There are several aspects that are assessed for validity. From this validation, an average validity value of 95.14% was obtained with the criteria